Επίδραση του εφελκυστικού ρήγματος στην ευστάθεια πρανών σε τρεις διαστάσεις - Γκότσης, Κωνσταντίνος Γ. (Τμήμα πολιτικών μηχανικών και μηχανικών γεωπληροφορικης, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Slope instabilities are a major hazard for human activities and many times are followed by the loss of properties and human lives. The necessity of evaluating the stability of slopes has lead to the development of new analysis methods, either referring to two or three-dimensions. Slopes show signs of distress some times before ultimate failure occurs and one such manifestation is the appearance of cracks along the slope crest. They are often the first visible indication that a slope may be unstable and their presence or absence is often adopted as a crude indicator of slope stability. Since the shear strength along a crack is zero the inclusion of a crack in the stability analysis often produces a factor of safety against failure which is lower than if the crack were omitted. The existence of such cracks indicates that in a certain zone the tensile stress exceeds the tensile strength of the soil. Tension cracks can affect the stability of slopes in a number of ways. The existence of a tension crack on a slope shortens the length of the slip surface and by this way reduces its resistance to failure. The water pressure acting on the crack face constitutes an additional driving force contributing to failure. Finally, the water inside the crack tends to soften the soil, degrading its strength properties. The present graduation thesis investigates the three dimensional effect of tension cracks in the stability of homogeneous slopes. The investigation is based on the proposed closed-form 3D analysis method by Pantelidis and Griffiths (2013b) and constitutes an original research which was done in cooperation with Dr. Lysandros Pantelidis and Elias Gravanis. This study constitutes the first attempt for evaluating the effect of tension cracks on slope stability in three dimensions. The problem was modeled in Wolfram Mathematica and all the possible failure mechanisms encountered in homogeneous slopes were studied. The slip surface was assumed to be a part of a spheroid and the tension crack was taken into account as part of a curved surface of a cylinder. Stability charts are given for the calculation of the stability number NF.
Keywords: Slopes; Tension Cracks; Slope Stability Indicator; Πρανή; Εφελκυστικό Ρήγμα; Δείκτης Ευστάθειας Πρανούς